Microbiological testing of adults hospitalised with community-acquired pneumonia: an international study. Issue 4 (8th October 2018) - Carugati, Manuela; Aliberti, Stefano; Reyes, Luis Felipe; Franco Sadud, Ricardo; Irfan, Muhammad; Prat, Cristina; Soni, Nilam J.; Faverio, Paola; Gori, Andrea; Blasi, Francesco; Restrepo, Marcos I.
This study aimed to describe real-life microbiological testing of adults hospitalised with community-acquired pneumonia (CAP) and to assess concordance with the 2007 Infectious Diseases Society of America (IDSA)/American Thoracic Society (ATS) and 2011 European Respiratory Society (ERS) CAP guidelines. This was a cohort study based on the Global Initiative for Methicillin-resistant Staphylococcus aureus Pneumonia (GLIMP) database, which contains point-prevalence data on adults hospitalised with CAP across 54 countries during 2015. In total, 3702 patients were included. Testing was performed in 3217 patients, and included blood culture (71.1%), sputum culture (61.8%), Legionella urinary antigen test (30.1%), pneumococcal urinary antigen test (30.0%), viral testing (14.9%), acute-phase serology (8.8%), bronchoalveolar lavage culture (8.4%) and pleural fluid culture (3.2%). A pathogen was detected in 1173 (36.5%) patients. Testing attitudes varied significantly according to geography and disease severity. Testing was concordant with IDSA/ATS and ERS guidelines in 16.7% and 23.9% of patients, respectively. IDSA/ATS concordance was higher in Europe than in North America (21.5% versus 9.8%; p<0.01), while ERS concordance was higher in North America than in Europe (33.5% versus 19.5%; p<0.01). Testing practices of adults hospitalised with CAP varied significantly by geography and disease severity. There was a wide discordance between real-life testing practices and IDSA/ATS/ERS guideline recommendations. Testing practices vary based on geography and disease severity, and IDSA/ATS/ERS testing recommendations are rarely followed http://ow.ly/80Iy30lxo1c